Protocol to generate dual-target compounds using a transformer chemical language model - Sanjana Srinivasan; Jürgen Bajorath (STAR Protocols)
Summary: Here, we present a protocol to generate dual-target compounds (DT-CPDs) interacting with two distinct target proteins using a transformer-based chemical language model. We describe steps for installing software, preparing data, and pre-training the model on pairs of single-target compounds (ST-CPDs), which bind to an individual protein, and DT-CPDs. We then detail procedures for assembling ST- and corresponding DT-CPD data for specific protein pairs and evaluating the model’s performance on hold-out test sets.For complete details on the use and execution of this protocol, please refer to Srinivasan and Bajorath.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.